PERANAN BAPAS TERHADAP ANAK YANG BERHADAPAN DENGAN HUKUM (PELAKU) - Jony Praditha, I Gede; Pasek Diantha, I Made (Kertha Wicara : Journal Ilmu Hukum, 2013)
Correction hall is a institution to implement the guidance of social service. This article contains some concerns regarding how Bapas role of law dealing with children (actors) and how the coaching process for children who are dealing with the law in bapas. The method used is the method of empirical research is the study of law with field research methods aimed at the written regulations or other legal materials, law while collecting techniques using library studies and interviews yangmana materials collected will be analyzed qualitatively. Analysis and findings obtained namely that Bapas have a very important role for children who are dealing with the law (the perpetrator). Bapas to the conclusion that the role of children in conflict with the law (the perpetrator) is mainly in the manufacture of social studies or case study which is a consideration for judges in deciding cases children properly and fairly as possible and the guidance of children in conflict with the law in Bapas done through three (3) stages: early stage, advanced stage and the final stage, with the intention of getting closer to God and sensitize clients to not repeat his crime.
Keywords: Bapas, Children in conflict with the law